1996
DOI: 10.1007/bf00311926
|View full text |Cite
|
Sign up to set email alerts
|

Obstruction of mechanical valve prostheses: Clinical diagnosis and surgical or nonsurgical treatment

Abstract: Twenty patients underwent nonsurgical and/or surgical treatment for obstruction of mechanical prosthetic valves. The obstructed prosthetic valve was in the aortic position in 11 patients, in the mitral position in 5, and in the tricuspid position in 4. Twelve patients had a bileaflet valve (3 aortic, 5 mitral, 4 tricuspid), and 8 had a tilting disk valve (all aortic). The diagnosis of prosthetic valve obstruction was made by cineradiography and echocardiography. Thrombolytic therapy was instituted in a series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…Replacement of the prosthesis is the most widely used approach but often simple removal of the thrombus (thrombectomy), in a normally functioning prosthesis is preferable [17]. It should be noted that the mortality rate of this surgery can be as high as 69%, depending on the NYHA functional class group [18,19].…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Replacement of the prosthesis is the most widely used approach but often simple removal of the thrombus (thrombectomy), in a normally functioning prosthesis is preferable [17]. It should be noted that the mortality rate of this surgery can be as high as 69%, depending on the NYHA functional class group [18,19].…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Based on our previous study, 4 PVO was suspected when VI was <0.35 on TTE and when persistent restriction of leaflet motion was observed on cineradiography with the measured opening angle ≥20°. 2 In this study, PVO was principally diagnosed based on the cineradiographic criteria because previous studies have demonstrated that PVO was detected accurately and far earlier on cineradiography than on TTE. 4,11,14,16…”
Section: Echocardiography and Cineradiographymentioning
confidence: 99%
“…Small valve size (B19 mm), a specific valve type (Carbomedics), an etiology of rheumatic valve disease, and young age at the time of AVR (\48.8 years) were found to be independent predictors of moderate to severe pannus. The incidence of prosthetic valve obstruction due to pannus has been known to be uncommon (0.1-4.5 % per patient-year in the aortic position) [3,12,16], but recent studies have found that prosthetic aortic valve obstruction caused by pannus is more frequent than previously reported and can be detected even in asymptomatic patients [17,18]. In our study, pannus formation was present in most cases (77.2 %), even in cases which showed a normal range of PG on TTE (71.4 %).…”
Section: Discussionmentioning
confidence: 99%
“…Pannus location was classified as focal and circumferential involvement, and focal involvement was subclassified according to a localization system based on the surgical view ( Fig. 1) [12,13].…”
Section: Image Analysismentioning
confidence: 99%